Portable teleprenatology system for midwives in rural areas - Yew, Hoe Tung; Yudha Aditya; Noraini Jalil; Hau, Yuan wen; Eko Supriyanto (Asian Research Publishing Network, 2015)
Decreasing Maternal Mortality Rate (MMR) to improve global health has been a big issue for most developing countries. Limited accesss to health care facilities especially for the poor in rural areas gives a hard declining for MMR around the globe. Midwife as the closest health provider for pregnant women in rural areas, is given a new solution to provide a better care toward community, hence improving maternal health and reducing MMR in the future. By using a computerized clinical pathway and an integrated ultrasound machine, a new portable teleprenatology system for midwives is being proposed. Multi-channel wireless network is also introduced in this system to prevent any interruptions during teleprenatology application.